Effect of Ground Waste Concrete Powder on Cement Properties - Xianwei Ma; Zhenyu Wang (Advances in Materials Science and Engineering)
The paste/mortar attached to the recycled aggregate decreases the quality of the aggregate and needs to be stripped. The stripped paste/mortar is roughly 20% to 50% in waste concrete, but relevant research is very limited. In this paper, the effects of ground waste concrete (GWC) powder, coming from the attached paste/mortar, on water demand for normal consistency, setting time, fluidity, and compressive strength of cement were analyzed. The results show that the 20% of GWC powder (by the mass of binder) has little effect on the above properties and can prepare C20 concrete; when the sand made by waste red clay brick (WRB) replaces 20% of river sand, the strength of the concrete is increased by 17% compared with that without WRB sand.